Implementasi Metode Project Development Routemap pada Proyek KPBU di Indonesia - Nadya Putri; Agung Budi Broto; Hari Purwanto; Roihans Muhammad Iqbal (PT Penjaminan Infrastruktur Indonesia (Persero), 2022)
The availability of road infrastructure is one of the important aspects of accelerating the national development process. With all the fiscal limitations in financing the need for large infrastructure provisions, an optimal funding strategy is needed to achieve development goals through alternative financing of the Public-Private Partnership (PPP) scheme to bridge the financing gap through investment. However, the realization of infrastructure investment is a complex matter, so a quality PPP project preparation and planning process is needed so the project visions can be achieved effectively and efficiently. This study aims to observe the application of the Project DevelopmentRoutemap Method on the Gedebage – Tasikmalaya – Cilacap Toll Road project which is a project carried out by PPP scheme. The Project Development Routemap Method assessed the complexity and strategic risk of a project and assessed the capability of key areas of responsisbility involved, as well as developed reccomendations and action plans as research outputs. Based on the result of the study, it was found that The Gedebage – Tasikmalaya – Cilacap Toll Road is a high-complexity project. The capabilities of the stakeholders including Sponsors (PJPK), Clients (BUJT), Aset Managers (Operators), and Markets (Service Providers) are currently working appropriately, but there are still some areas that need to be improved. Six areas needed improvement, and three practices that were appropriate and needed to be continued.